Compañeros Dirección Editorial. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2025)
René Muiños, Hilda Robles, Osman Guzmán Cruz y Lorena Picado
Colección Fototeca UNED
Keywords: Muiños Gual, René Agustín; Robles Sibaja, Hilda; Picado Camacho, Ana Lorena; Guzmán Cruz, Osman; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA